Applying C. elegans to the Industrial Drug Discovery Process to Slow Aging - Weinkove, David; Zavagno, Giulia (Frontiers in Aging, 2021)
The increase in our molecular understanding of the biology of aging, coupled with a recent surge in investment, has led to the formation of several companies developing pharmaceuticals to slow aging. Research using the tiny nematode worm Caenorhabditis elegans was the first to show that mutations in single genes can extend lifespan, and subsequent research has shown that this model organism is uniquely suited to testing interventions to slow aging. Yet, with a few notable exceptions, C. elegans is not in the standard toolkit of longevity companies. Here we discuss the paths to overcome the barriers to using C. elegans in industrial drug discovery. We address the predictive power of C. elegans for human aging, how C. elegans research can be applied to specific challenges in the typical drug discovery pipeline, and how standardised and quantitative assays will help C. elegans fulfil its potential in the biotech and pharmaceutical industry. We argue that correct application of this model and its knowledge base will significantly accelerate progress to slow human aging.